Pengalaman Konsumen Membangun Kepuasan dan Loyalitas Konsumen (Studi Empiris Pada Konsumen Paragon Mall Semarang - Ardyan, Elia (Graduasi: Jurnal Bisnis & Ekonomi, 2012)
This paper determine the effect of customer experience on customer satisfaction and loyalty. Population of this research arecustomer of Paragon Mall Semarang. The Number of Sample about 188 respondents. This research use Structural Equation model as its analysis. The result of this research are customer experience have positif and significants on customer satisfaction, customer satisfaction have positif and significant on customer loyalty, and customer experience have positif and significant on customer loyalty.